Model Inkuiri Terhadap Keterampilan Berpikir Kritis Ditinjau Dari Gaya Belajar Siswa Pada Pembelajaran Biologi - Lian Meliana; Ina Setiawati; Handayani Handayani (Journal of Natural Sciences, 2023)
Students are required to have competencies in accordance with the needs of the 21st century, one of which is critical thinking skills. However, within the scope of education in Indonesia, critical thinking skills have not been able to be developed due to the low diversity of the learning process and the teacher's ignorance of each student's learning style. The inquiry model is applied to facilitate students development of critical thinking skills. This study aims to analyze: 1) the effect of the inquiry learning model on students' critical thinking skills; 2) the influence of learning styles on students' critical thinking skills; and 3) the interaction between inquiry learning models and learning styles on students' critical thinking skills. This is quasi-experimental research. The research method used was quasi-experimental with Nonequivalent Pretest and post-test Control-Group Design. The data were analyzed using a two-way ANOVA test with a significance level of 5%. Based on the research results, the following results were obtained: 1) The inquiry learning model influences critical thinking skills; 2) Students' learning styles do not affect critical thinking skills; and 3) There is no interaction between the inquiry learning model and students' learning styles on critical thinking skills.